A Comparative Study of Language Maintenance among the Balinese and Dayak Ngaju through Identity and Core Cultural Practices - Maria Arina Luardini; Putu Sutama (Jurnal Kajian Bali (Journal of Bali Studies), 2025)
This article presents a comparative study of language maintenance among the Balinese in Bali and the Dayak Ngaju in Central Kalimantan, viewed through the lenses of identity and core cultural values. Both groups share similarities in their sociocultural Hindu traditions and social structures: the Balinese are organized through the banjar (community system), while the Dayak Ngaju communities are traditionally based along river streams. The findings show that Balinese language maintenance is stronger than that of Dayak Ngaju. Balinese is widely used across traditional and modern cultural domains, while Dayak Ngaju is mainly used in traditional contexts. Moreover, Balinese is reinforced by its own script and a distinct diglossia structure, features absent in Dayak Ngaju. This study suggests that effective local language maintenance should consider the vitality of core cultural practices within each domain.